2015
DOI: 10.1016/j.proci.2014.06.141
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular decomposition of formic and acetic acids: A shock tube/laser absorption study

Abstract: The thermal decomposition of formic acid (HCOOH) and acetic acid (CH 3 COOH), two carboxylic acids which play an important role in oxygenate combustion chemistry, were investigated behind reflected shock waves using laser absorption. The rate constants of the primary decomposition pathways of these acids:were measured using simultaneous infrared laser absorption of CO, CO 2 and H 2 O at wavelengths of 4.56, 4.18 and 2.93 microns, respectively. Reaction test conditions covered temperatures from 1230 to 1821 K a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
6
27
0
1
Order By: Relevance
“…Thus, the experimental values available so far cannot be taken as comparative data for this study since they all have been carried out at lower pressures ,,,,,. Nevertheless, the experimental activation energies obtained by fitting first‐order rates increase from 51.0 to 60.2 kcal mol –1 for diluted HCOOH mixtures in argon with total pressures of 1.0 and 6.5 atm, respectively . Hence, these values suggest that the high‐pressure limit will result in even larger activation energies.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, the experimental values available so far cannot be taken as comparative data for this study since they all have been carried out at lower pressures ,,,,,. Nevertheless, the experimental activation energies obtained by fitting first‐order rates increase from 51.0 to 60.2 kcal mol –1 for diluted HCOOH mixtures in argon with total pressures of 1.0 and 6.5 atm, respectively . Hence, these values suggest that the high‐pressure limit will result in even larger activation energies.…”
Section: Resultsmentioning
confidence: 98%
“…Several experimental and theoretical values can be found for activation energies of the reverse reaction, but there are large discrepancies among them. However, Elwardany et al . showed that the high‐pressure limit is still not achieved for the HCOOH decomposition direction at pressures as high as 6.5 atm.…”
Section: Resultsmentioning
confidence: 99%
“…The reactions of formic acid monomolecular decomposition were studied experimentally under low temperature in works [7,8] and under high temperatures in works [9][10][11][12]. According to the obtained results formic acid mostly decomposes via reaction HC(O)OH=CO+H2O whereas the reaction HC(O)OH=CO2+H2 has lower contribution.…”
Section: Introductionmentioning
confidence: 98%
“…These channels are shown below: HCnormalO2HnormalH2O+CO HCnormalO2HnormalH2+CnormalO2 HCnormalO2HOH+HCOThe decomposition reactions should be competitive, from comparison of their activation energies . However, experimental works have indicated that the dehydration is the preferred channel, and this fact still remains without a theoretical kinetic microscopic foundation. Takahashi et al have theoretically investigated this preference at the MP4/cc‐pVQZ//B4LYP/cc‐pVTZ level of theory and affirmed that canonical transition state theory cannot explain the dehydration preference.…”
Section: Introductionmentioning
confidence: 99%